Study on Validation of 20 m Progressive Aerobic Cardiovascular Endurance Run and Estimation of Maximal Oxygen Uptake in Adolescents - On Lee; Jin-Wook Chung (운동과학, 2019)
PURPOSE The purpose of this study was to investigate the validity of the 20 m PACER and to develop accurate and practical prediction models of maximal oxygen consumption using 20 m PACER. METHODS In total 407 (male 207, female 200) in middle and high school students participated in this study. Maximal oxygen uptake was measured using the maximal-graded exercise treadmill test. Sex, age, and anthropometrics variable were measured as potential predictors. Each test was conducted within a week interval, ensuring sufficient rest. Correlation analysis was performed to investigate the validity of 20 m PACER. Regression analysis was performed to develop the maximum oxygen uptake prediction equation using the 20 m PACER. The accuracy of prediction models was evaluated using R2, standard error of estimate (SEE), mean difference (MD), and limit of agreement (LoA%) against a criterion-measured of maximal oxygen uptake. RESULTS 20 m PACER was respectively .675 (.001) in male students .585 (.001) in female students showed reasonable validity. The equation of the following was developed (R2=0.77; SEE=3.58): VO2max=53.550+0.169 (20 m PACER)-0.333 (%body fat)+2.276 (sex)-0.080 (height). Gender has a value of 0 for men and 1 for women. CONCLUSIONS The prediction models included 4 variables as significant predictors of maximal oxygen uptake and had acceptable accuracy in a large sample of South Korean adolescent. Therefore, developed equation in this study is recommended for better estimation of cardiopulmonary fitness of middle and high school students.